National autonomies in the Far Eastern Republic: Post-imperial diversity management in pacific Russia, 1920-1922 - Sablin, Ivan (History and anthropology, 2017)
The Far Eastern Republic is discussed as a post-imperial structure intended to accommodate the multiple loyalties of the population. The establishment of national autonomies (Buryat, Korean, Ukrainian, Jewish and Tatar) was one way of managing the diversity of its population. Though never fully implemented, the project contributed to a new form of governance in a multi-ethnic polity.